Monitoring Kekenyalan Tahu Kedelai dengan Sensor Kapasitif Menggunakan Mikrokontroller Berbasis Android - Nanak Zakaria; Nurul Hidayati; Rizky Putri Nur Laili; Farida Arinie Soelistianto (Politeknik Negeri Cilacap, 2021)
Tofu has the best quality vegetable protein because it has the most complete amino acid composition and is believed to have high digestibility (85% -98%). According to SNI 01-3142-1998 and SII No. 0270-1990 testing criteria for soy tofu based on smell, taste, color, appearance, or texture. Tofu soybeans are prone to physical or texture damage due to factors such as inappropriate pH levels and insufficient storage which results in damaged tofu. Therefore in this study, it is proposed to determine the elasticity of soy tofu with the parameters tested are the pH level in the manufacture of soy tofu, the storage temperature, and the capacitance value to see how thick the tofu is with a capacitive sensor using the capacitor principle. Where the parallel plate capacitor is a capacitor consisting of two parallel metal plates. The test results of all sensors are sent to the database and will be displayed on the page on the Android application which will provide real-time sensor output information to the user. Based on the results of testing on this system using a pH sensor, the pH value is around 3-4 which indicates that the pH level used is very good for use in tofu processing, at pH 4.56 with storage at 29 ° C the highest elastic capacitance value is 3.58. In testing data delivery, the throughput value is 4336,217 b / s and the smallest delay value is 0.017ms because the smaller the delay value, the better the quality of data transmission because there will be no delay in sending data.